Management and Exploitation of Macroalgal Biomass as a Tool for the Recovery of Transitional Water Systems - Sfriso, Adriano; Mistri, Michele; Munari, Cristina; Buosi, Alessandro; Sfriso, Andrea Augusto (Frontiers in Ecology and Evolution, 2020)
Aquatic angiosperms favor the development of ecosystems services, the welfare of marine organisms and people. Generally the presence of angiosperms in transitional systems are indicators of good ecosystem status. Presently, these environments are densely populated and often are so highly degraded that angiosperms have almost disappeared, replaced by tionitrophilic macroalgae responsible of anoxic events that deteriorate the environment furtherly. Although this trend is hardly reversible because the anthropogenic impact is increasing and the restoring of damaged environments within a reasonable time is difficult, recent studies have shown that by managing the harvesting of the natural algal species of commercial interest a progressive environmental recovery is achievable. Biomass-harvesting can contribute both to the removal of high amounts of nutrients and the generation of economic revenues for a sustainable, self-financed environmental restoration. In fact, unlike clam-farming which destroys the seabed and re-suspends large amounts of sediments, the proper management of the macroalgal biomass, can favour the nutrient abatement and the recolonization of aquatic angiosperms which help restore the conditions necessary for the conservation of the benthic and fish fauna and birds, and produce valuable economic resources.